2016
DOI: 10.1016/j.parepi.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of ecbolin A and ecbolin B isolated from Ecbolium viride (Forsk.) Alston on dengue vector Aedes aegypti L. (Diptera: Culicidae)

Abstract: Ecbolin A and ecbolin B were isolated from ethyl acetate extract of Ecbolium viride (Forsk.) Alston root and evaluated for larvicidal and growth disturbance activities against Aedes aegypti L. (Diptera: Culicidae). For larvicidal activity, the third instar larvae of A. aegypti were exposed to different concentrations viz., 1.0, 2.5, 5.0 and 10 ppm for each compound. Among the two compounds screened, ecbolin B recorded highest larvicidal activity with LC50 and LC90 values of 0.70 and 1.42 ppm, respectively. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They are comparable to that of the insecticide temephos, which showed LC 50 values of 1.10 ppm. 50 Moreover, in the bioassays involving fourth instar larvae, it was observed that the toxicity is related to the exposure time to a toxic agent, a typical behavior of compounds with acute action.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…They are comparable to that of the insecticide temephos, which showed LC 50 values of 1.10 ppm. 50 Moreover, in the bioassays involving fourth instar larvae, it was observed that the toxicity is related to the exposure time to a toxic agent, a typical behavior of compounds with acute action.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%